1998
DOI: 10.1139/v98-176
|View full text |Cite
|
Sign up to set email alerts
|

Article

Abstract: The solution sol-gel method is used to produce thin films of photosensitive hybrid organic-inorganic glass on silicon. Glasses consisted of photoinitiator, methacryloxypropyltrimethoxysilane, methacrylic acid, and zirconium oxide. Clear, low optical loss films are obtained, indicating nanophase homogeneity in the samples. The nanocomposite films are shown to be suitable for fabricating optical components such as ridge wave guides and Bragg diffraction gratings. The increase in the refractive index of the glass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(61 citation statements)
references
References 0 publications
3
58
0
Order By: Relevance
“…The bands at 2890 and 2950 cm -1 are due to the asymmetric stretching of m s (CH 3 ) groups and to the symmetric m s (CH) stretching of the terminal methylene double bonds ( CH 2 ), respectively. [8] Accordingly, all these vibrational modes disappeared upon calcinations. The sharp band at 1730 cm -1 is ascribed to the C O carbonyl group.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The bands at 2890 and 2950 cm -1 are due to the asymmetric stretching of m s (CH 3 ) groups and to the symmetric m s (CH) stretching of the terminal methylene double bonds ( CH 2 ), respectively. [8] Accordingly, all these vibrational modes disappeared upon calcinations. The sharp band at 1730 cm -1 is ascribed to the C O carbonyl group.…”
Section: Resultsmentioning
confidence: 96%
“…[18,49,50] A further band at 450 cm -1 was also detected, which has been ascribed by other authors to the vibrations of the Si-O-Si network. [8] All vibrations typical of the organic components of the matrix could be detected in the as-prepared samples. The bands at 2890 and 2950 cm -1 are due to the asymmetric stretching of m s (CH 3 ) groups and to the symmetric m s (CH) stretching of the terminal methylene double bonds ( CH 2 ), respectively.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…[5][6][7][8][9][10] For the preparation of planar waveguides, photosensitive inorganic-organic hybrid films prepared by the sol-gel method have been studied extensively. [11][12][13][14][15][16][17][18][19] In these studies on inorganic-organic hybrid films, trimethoxysilylpropylmethacrylate TMSPM has been favored as a precursor since the methacrylate group easily polymerizes under UV irradiation or thermal treatment, 20 and the polymerization leads to an increase of refractive index to control waveguiding. We have reported on the preparation of inorganic-organic hybrid films from vinyltriethoxysilane VTES, allyltriethoxysilane or TMSPM, and zirconium n-tetrapropoxide modified with methacrylic acid, 21 and found that patterns with a width of about 10 mm and thickness of about 15 mm were formed by the etching of unirradiated region of the films.…”
Section: 4mentioning
confidence: 99%
“…The increase in refractive index of the SGHG films is mainly governed by photopolymerization of the organic component and polycondensation of the inorganic component. 10,11 However, the effect of the photoinitiator which has been usually 1-hydroxycyclohexyl-1-phenylketone (HCPK) sensitive to the light from the UV region on the refractive index change has been ignored since a small quantity of photoinitiator has been used. BDK is a common photoinitiator sensitive to 350 nm light to be used in a general mask aligner.…”
Section: Introductionmentioning
confidence: 99%